Electrical impedance tomography guided positive end-expiratory pressure titration in critically ill and surgical adult patients: a systematic review and meta-analysis - Yelin Gao; Huaiwu He; Yi Chi; Inéz Frerichs; Yun Long; Zhanqi Zhao (BMC Pulmonary Medicine)
Abstract Objective Electrical impedance tomography (EIT) has been used to titrate positive end-expiratory pressure (PEEP). This study aims to develop a comprehensive view of the efficacy and long-term prognosis of EIT-guided PEEP compared to other conventional approaches in various clinical scenarios, including patients with acute respiratory distress syndrome (ARDS), hypoxemic acute respiratory failure (hARF) and patients undergoing surgery under general anesthesia. Methods The literature search was conducted in PubMed, Web of Science, Embase, and Cochrane Library, from inception to July 30, 2023 (ARDS/hARF) and October 5, 2023 (surgery). The Cochrane risk of bias assessment and the methodological index for non-randomized studies were used for quality appraisal. The main outcomes were PEEP level, PaO2/FiO2 ratio, lung/respiratory system compliance (CL/Crs), driving pressure (ΔP), in-hospital mortality, and postoperative pulmonary complications (PPCs) in surgical studies. Results Four randomized controlled trials (RCTs), one historical control study, and six before-after studies of ARDS/hARF, as well as eight surgical RCTs, were retrieved. Subgroup analysis has been carried out and analysis of before-after studies was performed separately. Diverse PEEP strategies were adopted in the included studies, such as low/high PEEP-FiO2-table of ARDS-net, pressure–volume loop, and transpulmonary pressure. In ARDS/hARF studies, the EIT strategy did not result in considerably enhanced respiratory system mechanics, including comparable PaO2/FiO2 ratios, comparable ΔP, and increased CL/Crs. As for long-term prognosis, the rough overall meta-analysis showed decreased in-hospital mortality (risk ratio RR = 1.54, 95% CI = (1.09, 2.18), P = 0.01). In patients undergoing general anesthesia surgery, the EIT group demonstrated increased PaO2/FiO2 ratio, CL/Crs, and decreased ΔP versus the fixed 4 or 5 cmH2O PEEP. In postoperative prognosis, incidence of PPCs was generally comparable between the two groups. Conclusion The EIT-derived PEEP setting strategy might be associated with potential benefits in respiratory outcomes and prognosis in ARDS/hARF and surgical patients. Current data is insufficient to provide solid evidence.